The additional impact of simulation based medical training to traditional medical training alone in advanced cardiac life support: a scenario based evaluation - (:unkn) unknown (PHARMAMED MADO LTD, 2018)
Objectives. The principal aim of medical education is to provide medical student with the fundamental knowledge and required skills that can be specifically used in real-life conditions such as high-quality cardiopulmonary resuscitation (CPR). Traditional medical training (TMT) is an effective method in Advanced cardiac life support (ACLS) training. Simulation-based medical training (SBMT), with the advancements in technology, is a relatively new, but a preferred ACES training method since it implements a safe educational environment. We planned a scenario-based study to evaluate the additional impact of SBMT to TMT alone in ACES training. Methods. This before-after type, comparative, cohort study was performed in a simulation center. One hundred thirty-six 6th grade medical students who took ACLS training with TMT on their emergency medicine clerkship were enrolled in 34 teams. All students managed a specific ACLS scenario before and after SBMT with a high-fidelity manikin. All data regarding chest compression, airway management, defibrillation and drug administration were recorded by the sensors of the high-fidelity manikin. Results. Median age was 23 and 51.5% were male. After SBMT, we found significant increases in the successful CPR cycle rate and successful scenario completion rate (60.3%; 61.8%, respectively). Median time to chest compression (Tcc) and defibrillation (Tdef) were significantly decreased after SBMT (1 sec., 1 sec., respectively). For the adequacy of chest compressions, compression depth, recoil, and frequency are all significantly increased after SBMT 7.0 mm, 6.0 mm and 8.5/min, respectively. Conclusion. SBMT in combination with TMT is a promising ACLS training method when compared to TMT alone.
Keywords: simulation-based medical training; traditional medical training; high-fidelity manikin; CPR; ACLS; RESUSCITATION; PERFORMANCE; ARREST; CURRICULUM; RESIDENTS; FIDELITY; STUDENTS; QUALITY